Association between insulin resistance and C-reactive protein in a sample of non-obese Peruvians - Vera-Ponce, Víctor Juan (2021)
Background: The role of insulin resistance (IR) in chronic disease is largely due to the presence of low-grade inflammation, through proteins such as C-reactive protein (CRP). Although there is evidence of a relationship between IR and CRP, this is scarce in non-obese population. Objective: To evaluate the association between IR and CRP in a sample of non-obese Peruvians. Materials and methods: Cross-sectional analytical study of the secondary database of the PERU MIGRANT study. Results: We found a prevalence of IR of 3.72 %; while the prevalence of high CRP (≥ 3 mg/L) in the study subjects was 19.26 %. Patients with high CRP had 5.65 % higher frequency of having RI, compared to those with normal CRP (2.63 % vs 8.28 %; p= 0.003). Females had 1.49 % higher frequency of having IR, compared to males (4.51 % vs. 3.02 %; p= 0.336). Patients with high CRP had 214% higher frequency of having IR, compared to those without high CRP (PR=3.14, 95%CI: 1.52 - 6.50) and adjusting for confounding covariates (sex, age, BMI, group, smoking status, alcohol drinker and physical activity) high CRP had 198% higher frequency of having IR, compared to those without high CRP (PR=2.98, 95%CI: 1.49 - 5.96). Conclusions: In non-obese patients, the presence of CRP, in the absence of infectious pathology, could imply the existence of IR.